Losing work, moving on : international perspectives on worker displacement - Kuhn, Peter Joseph (W.E. Upjohn Institute for Employment Research, 2002)
And synthesis / Peter J. Kuhn -- Displaced workers in the United States and the Netherlands / Joap H. Abbring [and others] -- Worker displacement in Japan and Canada / Masahiro Abe [and others] -- They get knocked down. do they get up again? / Jeff Borland [and others] -- Worker displacement in France and Germany / Stefan Bender [and others] -- Employment protection and the consequences for displaced workers / Karsten Albœk, Marc Van Audenrode, and Martin Browning.